Stripe rust - Kang, Zhensheng; Chen, Xianming (Spring Nature, 2017)
This book comprehensively introduces stripe rust disease, its development and its integrated control. Covering the biology, genetics, genome, and functional genomics of the pathogen, it also discusses host and non-host resistance, their interactions with the pathogen and the epidemiology of the disease. It is intended for scientists, postgraduates and undergraduates studying stripe rust, plant pathology, crop breeding, crop protection and agricultural science. It is also a valuable reference book for growers, consultants and administrators in agricultural businesses and education.
Keywords: Stripe rust.; elektronické knihy; electronic books